Internet Nation: Identifying relevant factors for developing the business - to - consumer internet transactional space among Malaysian college students - Yusof, Norhafezah; Walters, Timothy (Universiti Utara Malaysia, 2014)
This study was a point- in- time benchmark of online shopping behaviour of mostly postgraduate college students in Malaysia designed to measured progress towards the e-commerce goals articulated in Vision 2020.Using an online convenience of 244 student students from three tertiary institutions, the study, which was conducted from 8th May 2013 to 29th July 2013, examined demographic variables and attitudes towards privacy, convenience, and in- store convenience.Among others, the study found that such findings presented herein include the fact that many students in this survey used the internet for information seeking rather than for buying and did not enjoy shopping online as much as they would shopping in a standard store. This study showed that in the Malaysia context, demographics such as gender and place of residence were salient.Women were more likely to enjoy shopping in a real store accompanied by their friends and were far less likely to use credit cards for any online purchase.Respondents from small towns were more likely to want to shop in a real store than were those from large towns. Besides providing several benchmarks, the study offered suggestions for SME's public policy makers and financial institutions to spur development of a more vibrant Internet- based business- to- consumer economy.Among these are recommendations for policy maker are increasing broadband availability and helping SME's develop a web presence and for SME's these include developing socially interactive websites, developing more secure methods of online payment, and implementing an integrated clicks- and- bricks strategy.